Liberia's First Civil War - Hogan, Edmund M., author.
1 online resource.
Keywords: "This book provides a comprehensive narrative history of Liberia's first civil war, from its origins in the 1980s right through the conflict and up to the peace agreement and conclusion of hostilities in 1997. The first Liberian Civil War was one of Africa's most devastating conflicts, claiming the lives of more than 200,000 Liberians, and sending shockwaves across the world. Drawing on a wide range of local and international sources, the book traces the background of the war and its long-term and immediate causes, before analysing the detail of the unfolding conflict, the eventual ceasefire, peace agreement and subsequent elections. In particular, the book shines a light on hitherto unseen first-hand Roman Catholic indigenous and missionary sources, which offer a rare intimacy to the analysis. Detailing the impact of Liberia's individual warlords and peacemakers, the book also explains the roles played by non-governmental agencies, national, regional and international actors, by the UN, ECOWAS and the Organisation of African Unity, and by nations with special interests and influence, such as the USA and other West African states. This book's detailed narrative analysis of the Liberian conflict will be an important read for anyone with an interest in the Liberian conflict, including researchers within African studies, political science, contemporary history, international relations, and peace and conflict studies"--